NEWEST TECHNOLOGIIES IN CELIAC TRUNK ANEURYSMS TREATMENT - O. V. Galimov; V. V. Plechev; V. Sh. Ishmetov; V. O. Khanov; R. E. Abdrakhmanov; T. R. Ibragimov; S. I. Blagodarov; A. R. Gilemkhanov (Креативная хирургия и онкология)
Artery aneurysms of pool celiac trunk and superior mesenteric artery are not often in clinical practice. Often, the first clinical manifestation of the aneurysm is a hemorrhagic shock which proceed from its rupture. The risk of aneurysm rupture doesn’t depend on their size, ranging from 3% to 10%. But the mortality from aneurysm rupture can be reaches 36%. As we know well that the aneurysm ruptures has a high rate of mortality, treatment as symptomatic as asymptomatic aneurysms are essential. The authors of the article represent the demonstration of successful endovascular treatment of aneurysms splenic artery and posttraumatic aneurysm of common hepatic artery using modern embolization materials. In the first case performed embolization of lumen aneurysm by embolization coil with next installation in the lumen of the artery stent graft, in the second case – the feeding artery was embolized by microemboles. Nowadays, the medical instruments for X – ray surgical interventions allow you to perform a complete embolization of pathological structures such as aneurysms of the main arteries of the celiac trunk. Thanks to low level of interventions endovascular therapies can be related to the method of choice in the treatment of many surgical diseases in compulsory with the open methods of operation.